Simulation Of Web Page Combination And User Scaling Approach For Ad Hoc Social Network (Journal of Namibian Studies : History Politics Culture, 2023)
User scaling is an important function relating to web page access and retrieval. In an ad hoc social network when the number of visitors grows, so does scaling to maintain the operational speed for optimal efficiency. Users usually surf through many web sites in order to obtain the required information. Obviously, collecting this information is a tedious and time-consuming process. We set out to lessen this difficulty by attempting to combine the information from various sites into one common place arranged by content classification, whereby the information can be browsed and extracted methodically. We propose a novel conceptual model encompassing both technical solubility and cost involved. The method is tested on functional viability for an ad hoc social network using a simulation run. We find that for low to medium visitor volumes, the proposed method operates slightly better than performing the task in the usual way. For a large visitor volume, the benefits are considerable. We hope that this prospectus will instil more effective way-of-working to access and retrieve information for social networking from the internet.